Pelatihan dan Pendampingan UMKM di Desa Petak Gianyar - Dwitrayani, Made Christin; Asana, Gde Herry Sugiarto; Tabita, I Dewa Ayu Tita Permana; Agustini, Ni Putu Widya; Sari, Ni Putu Sukma Artadhi; Sukmaningsih , Kadek (Universitas Triatma Mulya, 2025)
Group 8's study for the Thematic Real Work Lecture (KKNT) activity focused on UMKM Training and Mentoring Activities in Petak Gianyar Village. The purpose of this research is to support Small and Medium Enterprise (UMKM) actors in Petak village by offering proposals, solutions, and strategies to expand their enterprises. To examine the efforts of UMKM actors, qualitative approaches were used in this KKNT activity. The UMKM players in Petak village are the subject of the research because they are interested in the circumstances, particularly with regard to the challenges they encounter in operating their businesses. Visiting UMKM, finding out about the challenges they encounter in operating their business, and offering solutions to their problems are all examples of training and mentoring activities that are conducted. It is envisaged that Petak village UMKM will profit from this action. and ideally UMKM players would be able to run their businesses consistently after completing this training and mentoring.